Eradication of Mycoplasma hyopneumoniae from Infected Swine Herds Joining the LSO 2000 Health Class - Heinonen, M. (Acta Vet Scand, 1999)
The study was conducted in order to determine if eradication of swine enzootic pneumoniae (SEP) had succeeded with different variants of partial depopulation during the eradication programme on swine farrowing farms joining a health class, LSO 2000. The farms in the health class need to be free from swine enzootic pneumoniae, swine dysentery, sarcoptic mange and atrophic rhinitis. Twenty-one eradication attempts for M. hyopneumoniae were carried out using different variants based on separating adult animals for 2 weeks from infected young pigs which were not returned to the herd. The infected young pigs were kept in the same building (variant 1) in 4 herds and on the same compound (variant 2) as disease-free pigs in 12 herds. The infected young pigs were finally all sold. In 5 herds only adult animals were present during the eradication (variant 3). The eradication attempt succeeded in 81% and failed or remained uncertain in 19% of the herds. The result was confirmed with 1) frequent clinical follow-up of the health status in the herds (both the farrowing and the finishing units) joining the LSO 2000 health class 2) milk and/or blood serology. Possible causes of the failure of the eradication attempt were described: a short distance between infected and uninfected animals, the time period between diagnosis of SEP and initiation of the programme, the age of the youngest animal kept on the farm, the period of time when animals with different status were reared close to each other, the medications used, the cleaning of the facilities during the programme and the season. Further, a good co-operation between the farmer, the local veterinarian and the animal health service of the slaughterhouse was an essential part of the initiation and the follow-up of the programme. The secondary aim of the study was to collect information about the expenses during the programme. Only 57% of the farmers gave some estimates for the expenses on their farms. For variants 1, 2 and 3 the expenses were 879, 1110 and 1274 FIM per sow (1 USD = 5.5 FIM), respectively (p>0.1).